2010
DOI: 10.1007/s12650-009-0005-6
|View full text |Cite
|
Sign up to set email alerts
|

Flow characteristics around a square cylinder with changing chamfer dimensions

Abstract: It is known that for a square cylinder subjected to uniform flow, the drag force changes with the angle of attack. To clarify the flow characteristics around a square cylinder with corner cutoffs, we measured the drag coefficient and the Strouhal number for changing chamfer dimensions. We analyzed the flow around a square cylinder with corner cutoffs by applying the RNG k-e turbulent model, and investigated the surface flow pattern using visualization by means of the oil film and mist flow method. From these r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The drag coefficient reductions for the chamfered and the round corner models are 18 and 29%, respectively. These results agree qualitatively with Tamura and Tetsuya (1999) and Yamagishi et al (2010). Results for wind speed of 40 m/s shows that though the chamfered corner model results were insensitive to Re effects, the round corner model results were sensitive to Re effects.…”
Section: Effect Of Corner Modificationsupporting
confidence: 81%
“…The drag coefficient reductions for the chamfered and the round corner models are 18 and 29%, respectively. These results agree qualitatively with Tamura and Tetsuya (1999) and Yamagishi et al (2010). Results for wind speed of 40 m/s shows that though the chamfered corner model results were insensitive to Re effects, the round corner model results were sensitive to Re effects.…”
Section: Effect Of Corner Modificationsupporting
confidence: 81%
“…Visualization techniques also confirmed that the drag coefficient increased as the width of the wake behind the cylinder became larger Yamagishi et al (2010). It should be noted that in tall building design, corner geometry changes have played an important role in reducing wind loads.…”
Section: Corner Modificationmentioning
confidence: 66%
“…Tamura and Miyagi (1999) concluded that corner modification decreases the wake width and promotes reattachment resulting in reduced drag forces. to approximately 1.5 for C5 (C/d = 0.167) Yamagishi et al (2010). Visible flow patterns obtained by Yamagishi et al (2010) using a propylene glycol mist tracer showed that the separation area of C3 was smaller than the areas for the sharp edge square and C5.…”
Section: Corner Modificationmentioning
confidence: 90%
See 1 more Smart Citation